Bimetallic (or Multimetallic) Synthesis of N-Heterocycles - Reis, Ana Rita (2023)
This research was funded by Fundação para a Ciência e Tecnologia (FCT, PTDC/QUI-QOR/0712/2020) and fellowships PD/BD/05960/2020 (D.R.) and 2022.12365.BD (N.V.). Publisher Copyright: © 2023 by the authors.